Acute hamstring injuries in Swedish elite football: a prospective randomised controlled clinical trial comparing two rehabilitation protocols - Askling, C. M.; Tengvar, M.; Thorstensson, A. (British Journal of Sports Medicine, 2013)
Background: Hamstring injury is the single most common injury in European professional football and, therefore, time to return and secondary prevention are of particular concern.